The Sovereign-Bank Nexus in EMDEs : What Is It, Is It Rising, and What Are the Policy Implications? - Feyen, Erik; Zuccardi, Igor (World Bank, Washington, DC, 2019)
This paper explores the sovereign-bank nexus in emerging markets and developing economies: the interconnectedness between the health of the sovereign and the banking system. Data from 140 emerging markets and developing economies suggest that this nexus is rising. First, banks have increased their exposure to their sovereigns in the past decade. Second, government debt has grown, and fiscal positions have deteriorated, raising the specter of sovereign stress. Third, banking system assets and bank credit to the private sector have steadily increased, which may restrict the sovereign's capacity to contain a banking crisis. Fourth, empirical evidence from 36 emerging markets and developing economies documents the existence of the nexus and suggests that it has increased recently. However, deeper country analysis is required for a better understanding of the sovereign-bank nexus, given country idiosyncrasies, including the structure of sovereign debt and the composition of the investor base, and data lags and opacities. To minimize the adverse effects of the sovereign-bank nexus, efforts should be focused on maintaining fiscal and bank buffers, strengthening surveillance and supervision of the banking system, improving transparency and data quality of bank-sovereign linkages, better addressing the regulatory treatment of the sovereign exposures and government support of the banking sector, and carefully evaluating the policy trade-offs in the sovereign-bank nexus.